Analysis of the spatial distribution of the serve and the type of serve-return in elite table tennis. Sex differences - Pradas, Francisco; Toro-Román, Víctor; Castellar, Carlos; Carrasco, Luis (Frontiers in Psychology, 2023)
Serve and return of the serve are among the most critical technical-tactical factors influencing performance in table tennis (TT). The present study aimed to analyse sex differences in the spatial distribution of serve and serve-return in elite TT players. A total of 48 elite TT players (men: n = 24; women: n = 24) participated in the investigation. A total of 24 matches were recorded and examined, analysing 1,177 plays and 5,319 strokes in the men’s competition and 950 games and 5,097 strokes in the women’s competition. Technical actions were analysed using an observation tool validated by two expert TT coach with a high level of agreement (K > 0.80). Men distributed their serves over zones 1 and 2 of the table, while women more frequently selected zone 5 (p < 0.05). In men, 30.1% of the serves were near the net, 63.6% in the middle zone of the table and 6.2% in the end zone of the table, while in women, these values were 10.9%, 67.2%, and 21.8%, respectively. As for the technique of the serve-return depending on the zone of the service, in men the action of the cut from zone 1 and 2 predominated, while in women this technique was more frequent from zone 5 (p < 0.05). On the other hand, the serve-return with the flip technique in zone 1, 3 and 4 was more frequent in men (p < 0.05). As for the return of the serve with the topspin technique, there were differences in zone 3, being more frequent in men (p < 0.05). Finally, the serve return with cut and defensive serve-return techniques in zones 3, 4, 5, and 6 were more frequent in women (p < 0.05). There are differences between sexes in service and return of serve actions during a match in elite players.